2020
DOI: 10.1155/2020/7207354
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Diterpenoids fromCelastrus orbiculatusin Lipopolysaccharide-Stimulated RAW264.7 Cells

Abstract: Celastrus orbiculatus Thunb has been known as an ethnopharmacological medicinal plant for antitumor, anti-inflammatory, and analgesic effects. Although various pharmacological studies of C. orbiculatus extract has been reported, an anti-inflammatory mechanism study of their phytochemical constituents has not been fully elucidated. In this study, compounds 1–17, including undescribed podocarpane-type trinorditerpenoid (3), were purified from C. orbiculatus and their chemical structure were determined by high-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Additionally, COE promotes apoptosis by regulating cell proliferation, migration, invasion, apoptosis, autophagy, and cycle distribution. These findings suggest that COE may be a potential therapeutic agent for the treatment of various cancers ( Qian et al, 2012 ; Zhang et al, 2012 ; Li et al, 2014 ; Yang et al, 2016 ; Wang et al, 2017a ; Wang et al, 2018 ; Jang et al, 2020 ). In this study, we demonstrated that COE could also interfere with Burkitt lymphoma cells and inhibit their proliferation.…”
Section: Discussionmentioning
confidence: 85%
“…Additionally, COE promotes apoptosis by regulating cell proliferation, migration, invasion, apoptosis, autophagy, and cycle distribution. These findings suggest that COE may be a potential therapeutic agent for the treatment of various cancers ( Qian et al, 2012 ; Zhang et al, 2012 ; Li et al, 2014 ; Yang et al, 2016 ; Wang et al, 2017a ; Wang et al, 2018 ; Jang et al, 2020 ). In this study, we demonstrated that COE could also interfere with Burkitt lymphoma cells and inhibit their proliferation.…”
Section: Discussionmentioning
confidence: 85%
“…Compounds 494 – 496 and 500 demonstrated moderate inhibitory activities against NF-κB activation in RAW264.7 macrophages, with IC 50 values of 15, 25, 19, and 4 μM, respectively [ 149 , 150 , 151 ]. Compound 8 was the most effective compound in inhibiting LPS-induced nitric oxide (NO) production (IC 50 = 3.56 μM) in T. orientalis .…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…The NF-κB pathway and additionally ERK1/2 and JNK were inhibited by Aster incisus [ 109 ] and Fructus sophorae [ 110 ] extracts; ERK1/2 and p38 were attenuated by Hibiscus syriacus [ 111 ] and Rodgersia podophylla [ 112 ] extracts; JNK and p38 were decreased by Populus deltoides [ 113 ] and Xanthii fructus [ 114 ] extracts in macrophage cell lines. Furthermore, deoxynimbidiol and trinorditerpenoid, diterpenoids from Celastrus orbiculatus [ 115 ], torilin, a sesquiterpene obtained from Torilis japonica [ 96 ], shikonofuran E, a phenolic compound isolated from Onosma paniculatum [ 116 ], scandoside, an iridoid from Hedyotis diffusa [ 117 ], bellidifolin, a xanthone from Swertia chirayita [ 118 ], 1-carbomethoxy-β-carboline, an alkaloid from Portulaca oleracea [ 119 ] and strictosamide, an alkaloid from Nauclea officinalis [ 120 ] inhibited both NF-κB and MAPK signaling ( Figure 3 ).…”
Section: Plants and Their Active Compounds As Modulators Of Macropmentioning
confidence: 99%